2022
DOI: 10.1073/pnas.2119467119
|View full text |Cite
|
Sign up to set email alerts
|

Structural conservation among variants of the SARS-CoV-2 spike postfusion bundle

Abstract: Significance Emergence of viral pathogens necessitates new approaches to study viral fusion and entry into host cells. A key step in mediating fusion involves the formation of a six-helix bundle within the spike protein. Rapid structural characterization of this state has been difficult, hindering understanding of emerging variants. We developed a method to efficiently determine high-resolution bundle structures by molecular scaffolding and cryogenic electron microscopy. Using this method, we determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 66 publications
(91 reference statements)
3
46
0
Order By: Relevance
“…For the Delta variant, the featured mutation of D950N (24410 G > A) was selected as the target site, because this mutation mapped to the trimer interface, suggesting that this mutation may contribute to the regulation of spike protein dynamics [ 39 ]. Furthermore, the Omicron variant and its subtype BA.1 contains mutation sites including N969K (24469 T > A, both Omicron and BA.1) and L981F (24503 C > T, BA.1 only) [ 40 ], and those sites were selected to distinguish them according to variants using MOPCS (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the Delta variant, the featured mutation of D950N (24410 G > A) was selected as the target site, because this mutation mapped to the trimer interface, suggesting that this mutation may contribute to the regulation of spike protein dynamics [ 39 ]. Furthermore, the Omicron variant and its subtype BA.1 contains mutation sites including N969K (24469 T > A, both Omicron and BA.1) and L981F (24503 C > T, BA.1 only) [ 40 ], and those sites were selected to distinguish them according to variants using MOPCS (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous high-resolution structures of the post-fusion HR1HR2 bundle of the Wuhan-Hu-1 strain of SARS-CoV-2 (GISAID accession ID: EPI_ISL_402124, here referred to as Wuh) revealed an overall six-helix bundle architecture in which the HR1 α-helices form a core with grooves into which the HR2 segments lie (PDB IDs 6lxt, 6m1v, 7rzq) (9, 15, 16). The cryo-EM structure of this HR1HR2 bundle (PDB ID 7rzq) (16) clarified several sidechain positions at high resolution and revealed that the N-terminal region of the HR2 fragment (residues 1164–1200) forms a well-defined extended conformation. Based on this observation, we further extended the N-terminal region, beginning at residue 1157, and determined the cryo-EM structure of this extended HR1HR2 complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cryo-EM structure of the longHR2_45 bound to HR1 was determined following a molecular scaffolding method described previously (16). Briefly, the scaffolded HR1HR2 complex was generated by co-expressing the scaffolded HR1 and SUMO-tagged longHR2_45 in E. coli BL21(DE3) using auto-inducing LB medium (30), followed by Nickel affinity chromatography and size exclusion chromatography (SEC) with a Superose 6 Increase 10/300 GL column in 25 mM HEPES-Na, pH 7.4, 150 mM NaCl, 0.5 mM EDTA, 0.5 mM TCEP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the postfusion state) relative to the bent prefusion state. [15][16][17] When this occurs away from a host cell membrane, it permanently disarms the spike trimer and also exposes more epitopes for binding of additional NAbs.…”
Section: Introductionmentioning
confidence: 99%